V-Movement, subject clitics, and inversion - Edward Rubin (Isogloss, 2025)
Building on new evidence from Bolognese, this paper proposes an account for the appearance and distribution of φ-related subject clitics both within and among Gallo-Italic grammars that relies only on independently motivated mechanisms. It notes problems for previous accounts that include additional subject clitic specific functional heads and varying height of head-movement. Instead, it proposes that subject clitics depend on standard Agree, and that they are a consequence of an extra uφ (“agreement doubling”) beyond the one inherited from C. Inversion in interrogatives is purely syntactic, and follows from strictly cyclic head-movement of V up to C. These two separate uφs underlie the distinct patterns of syncretisms and gaps in paradigms for verbal agreement suffixes and subject clitics in particular grammars, and for generalizations among them. Furthermore, gaps in a paradigm of subject clitics, like gaps in an agreement paradigm, do not imply a lack of Agree, but only a lack of overt exponents. Independently motivated syntactic mechanisms thus feed independently motivated morphological mechanisms. The syntax determines word/morpheme order, while morphophonology determines their realization.